1983
DOI: 10.4141/cjss83-021
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Nutrition of Soybeans as Affected by Placement of Fertilizer Phosphorus

Abstract: Bulr-eN, C. W., Sopsr., R. J. eNo Berlsy, L. D. 1983. phosohorus nutrition of soybeans as affected by placement of fertilizer phosphorus. Can. J. Soil Sci.63 199-210. Growth chamber and field experiments were conducted on Southern Manitoba soils, low in available soil phosphorus, to investigate the effects ofvarious placement methods and levels of phosphorus fertilizer on soybean (Glycine max (L.) Merrill'Maple Presto'). It was found that soybean responded well to applied phosphorus on low-P soil in grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 4 publications
0
9
2
Order By: Relevance
“…The results obtained from the P sites did not agree with those of Bullen et al (1983), who concluded that soybean yield increases were higher with banded fertilizer P when compared with broadcast applications. Broadcast K increased yields in only one of four site‐years in these studies.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The results obtained from the P sites did not agree with those of Bullen et al (1983), who concluded that soybean yield increases were higher with banded fertilizer P when compared with broadcast applications. Broadcast K increased yields in only one of four site‐years in these studies.…”
Section: Discussioncontrasting
confidence: 72%
“…Prummel (1957) found banded K fertilizer in cereals was 3.65 times more effective than broadcast, which he attributed to reduced K fixation. Furthermore, Bullen et al (1983) reported that soybean yield increases from P applied in a band near the seed were superior to those resulting from broadcast applications. In contrast, Lutz and Jones (1974) have shown that broadcast application of P would improve soybean yields when compared with deep placement.…”
mentioning
confidence: 99%
“…Provided placement of fertilizer in furrows adjacent to the seed does not cause toxicity, fertilizer use efficiency should be increased as compared with broadcasting (Bullen et al, 1983). In soils in Bangladesh where the recommended rate of P application for lentil and chickpea for broadcast application is 20 kg P ha −1 , preliminary studies by the authors at the locations of seed rate trials (Table 2) indicated a marginal yield reduction of these crops sown by VMP with strip tillage when the P rate was halved.…”
Section: Fertilizermentioning
confidence: 99%
“…According to Abuli et al [27], DAP is the best source for supplying phosphorous nutrients to soybean crops. Likewise, in an experiment performed by Bullen et al [28], it was found that banding applications of phosphorous fertilizers were more effective than broadcasting in increasing growth, seed yield, and phosphorous uptake of soybeans. Growth chamber and field experiments were carried out in Southern Manitoba in low soil available phosphorous to investigate the various placement methods and level of phosphorous in soybean.…”
Section: Phosphorusmentioning
confidence: 92%